Relationship between Context of Origin and Academic Achievement upon Completing Elementary School - Aldo Bazán-Ramírez; Eduardo Hernández-Padilla; César A. Hernández-Rodríguez; Eneida Ochoa-Avila (Universidad Autónoma de Baja California, 2020)
This study was conducted with the goal of explaining the effect that students' context of origin may have on three indicators of academic achievement as they complete elementary school: performance in an assessment of expected learning outcomes in reading and writing skills, and expected learning outcomes in four mathematical skills; achievement in the ENLACE test (in Spanish and mathematics); and the average grade assigned by the class teacher at the end of the school year. The sample was made up of 76 students from private schools, 103 from public schools in urban areas, and 123 students from indigenous schools and a public school in a rural area. The findings show that 1) there are significant differences in student performance in the three indicators of achievement, according to context of origin; 2) the differences based on context of origin vary depending on the difficulties and characteristics of each type of expected learning outcome; and 3) the structural relationships between the three indicators of academic achievement vary depending on the context of origin and the subject area evaluated.